PENGARUH IKLIM KETERLIBATAN ORGANISASI DAN KETERLIBATAN KARYAWAN TERHADAP KINERJA ORGANISASI SEKTOR INDUSTRI MANUFAKTUR INDONESIA - Sutopoh*, Sutopoh; Machmud, Fajar; Rahayu, Agus; Wibowo, Lili Adi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
Organizations increasingly rely on knowledge creation and human development for optimal and sustainable growth. Employee engagement is a significant construct that touches almost all aspects of human resource management as we know it today. This study aimed to examine the effect of organizational climate on employee involvement in the manufacturing industry sector in the Karawang Industrial Estate, West Java, Indonesia. The population in this study is a Manufacturing Company in the Karawang Industrial Estate, Indonesia. The intended respondents are Managers or Supervisors in the company with 75 respondents. The analytical technique used in this research is partial least square (PLS-SEM). The results of this study indicate that there is a positive and significant effect of the two variables studied on Organizational Performance. Keywords: Organizational Engagement Climate, Employee Engagement, Organizational Performance, Manufacturing Industry Sector, Karawang